Gender-Responsive Budgeting: The Case of a Rural Local Body in Kerala - Nisha Velappan Nair and John S. Moolakkattu (SAGE Open, 2018)
This article discusses gender-responsive budgeting (GRB) at the local level in Kerala by studying a village panchayat, the lowest tier of rural local government. GRB of a rudimentary form, known as Women Component Plan (WCP), had been in existence at the local level for the last 20 years as a key feature of participatory planning. The study adopts a fourfold classification of all projects implemented in the panchayat on the basis of their gender friendliness and calculates allocation and expenditure under each of these categories. The data on which the article relies relate to the expenditure incurred under the annual plans rather than budgets, which are based on inflated and unreliable data. The article ends by making some observations based on the data and the overall experience of Kerala in gender budgeting.